PEMANFAATAN PUPUK HAYATI DAN BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata) - A. Marthin Kalay; Reginawanti Hindersah; Irene A. Ngabalin; Marina Jamlean (Agric, 2020)
Growth and production of corn plants require land with sufficient nutrients. Utilization of biological fertilizers and organic materials carried out with the aim of increasing the yield of corn. The treatments that were tried were the provision of compost, livestock manure, compost and livestock manure, each of which was added by spraying a consortium of biological fertilizer. The experiment was designed using a randomized block design with five replications. The results showed that the application of organic-based fertilizers affected plant height from 17 - 49 days after planting, weight of fruit with kelobot, weight of cob and ear length. Provision of compost or livestock manure and added with a biological fertilizer consortium by spray gives a higher effect compared to the provision of compost or livestock manure which is not added to the consortium of biological fertilizer. To increase the productivity of maize plants it is recommended to use a consortium of biological fertilizers applied by spraying at intervals of seven days until the plants are 49 days after planting.